Black Fruit Plant (Haplolobus Monticola) Ethanolic Extract as a Good Source of Chemical Compound Content with The Potential as A Safe Antioxidant and Antibacterial Agent - Lestari, Agnes Dyah Novitasari; Toja, Yori Turu; Ungirwalu, Antoni; Ramlah, Ramlah -; Somar, Evelina; Murtihapsari, Murtihapsari - (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2024)
Black fruit is a native Papuan plant that faces extinction if it is not propagated. The availability of scientific information on the potential use of black fruit can help proliferate this plant. This study investigates the potential of black fruit plants in the leaves and flesh of the fruit using extraction, characterization, and extract activity testing. Extraction was carried out by maceration using a 96% ethanol solvent. Characterization was carried out by FTIR, UV-Vis spectrophotometers, and phytochemical screening. The antioxidant activity test was carried out by the DPPH method, the antibacterial test was carried out by the well diffusion method, and the toxicity test was carried out by the BSLT (Brine Shrimp Lethality Test) method. The results showed that the ethanol extract of black fruit flesh separated into two layers when stored in the refrigerator, while the leaf extract did not. Leaf extract is richer in phytochemical content compared to fruit flesh. Antioxidant and antibacterial activities were higher in leaf extracts than in fruit pulp extracts. Toxicity test results showed that the ethanol extract of black fruit leaves has the potential to be used as a food additive for antioxidant and antibacterial properties. The potential benefits of the ethanol extract of black fruit leaves and flesh can encourage cultivation and post-harvest management of this plant.